2015
DOI: 10.1007/978-3-319-18368-8_7
|View full text |Cite
|
Sign up to set email alerts
|

Data Integration to Create Large-Scale Spatially Detailed Synthetic Populations

Abstract: Many planning support systems and, indeed, some 'smart city' initiatives begin with time consuming efforts to integrate cross-agency data describing current conditions in sufficient detail to support 'what-if' exploration of urban development options. Integrating data from different sources has become increasingly challenged as available datasets, and the relevant urban modeling efforts, become more disaggregated and spatial-temporally detailed. Open data initiatives, with unprecedented amounts of embedded geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…This study used the floor-area ratio (FAR) to indicate land use densities. Our FAR values were derived from a building database synthesizing a variety of datasets using the methodology proposed by Zhu and Ferreira (2015). We measured the land use density in four categories: public residential (i.e., HDB, named after the Housing and Development Board), private residential, commercial, and industrial areas.…”
Section: The Impact Of the Built Environmentmentioning
confidence: 99%
“…This study used the floor-area ratio (FAR) to indicate land use densities. Our FAR values were derived from a building database synthesizing a variety of datasets using the methodology proposed by Zhu and Ferreira (2015). We measured the land use density in four categories: public residential (i.e., HDB, named after the Housing and Development Board), private residential, commercial, and industrial areas.…”
Section: The Impact Of the Built Environmentmentioning
confidence: 99%
“…Besides trip data, SimMobility includes a database of buildings in Singapore 56,57 . We estimate current parking supply from this database and publicly available data from official sources: the minimum parking requirements published by the Land Transport Authority (LTA) 58 , the list of parking spaces managed by the Urban Redevelopment Authority (URA) 59 , and the aggregate number of parking spaces managed by the Housing Development Board (HDB) 60 .…”
Section: Methodsmentioning
confidence: 99%
“…Although a certain level of interpretability could be maintained, ontology based 107 approaches are constrained to specific systems like buildings (Balaji et al 2016) example, recent work has demonstrated a strong link between transportation demand and energy 111 consumption in buildings (Karan et al, 2015). Moreover, a limitation of ontology based data integration 112 methods is that they must be fully expressive when defining their metadata schema and thus cannot adapt 113 easily to new urban data streams and types (Sinnott et al 2012;Zhu and Ferreira Jr 2015). While domain 114 centric methods are effective for data integration within individual system domains, they are limited in their 115 ability to both account for interactions across systems (extensibility) and easily adapt to growing and quickly 116 changing urban data streams (scalability).…”
Section: Domain Centric Integration Methods 95mentioning
confidence: 99%